Extensive Exon Reshuffling Over Evolutionary Time Coupled to Trans-Splicing in Drosophila - Labrador, Mariano; Corces, Victor G. (Genome Research, 2003)
The relative position of exons in genes can be altered only after large structural mutations. These mutations are frequently deleterious, impairing transcription, splicing, RNA stability, or protein function, as well as imposing strong inflexibility to protein evolution. Alternative cis- or trans-splicing may overcome the need for genomic structural stability, allowing genes to encode new proteins without the need to maintain a specific exon order. Trans-splicing in the Drosophila melanogaster modifier of mdg4 (mod[mdg4]) gene is the best documented example in which this process plays a major role in the maturation of mRNAs. Comparison of the genomic organization of this locus among several insect species suggests that the divergence between the lineages of the mosquito Anopheles gambiae and D. melanogaster involved an extensive exon rearrangement, requiring >11 breakpoints within the mod(mdg4) gene. The massive reorganization of the locus also included the deletion or addition of a new function as well as exon duplications. Whereas both DNA strands are sense strands in the Drosophila gene, the coding region in mosquito lays in a single strand, suggesting that trans-splicing may have originated in the Drosophila lineage and might have been the triggering factor for such a dramatic reorganization.
10.1101/gr.1440703